Contribution of hand and foot force to take-off velocity for the kick-start in competitive swimming - Takeda, T.; Sakai, S.; Takagi, H.; Okuno, K.; Tsubakimoto, S. (Journal of Sports Sciences, 2017)
This study examines the hand and foot reaction force recorded independently while performing the kick-start technique. Eleven male competitive swimmers performed three trials for the kick-start with maximum effort. Three force platforms (main block, backplate and handgrip) were used to measure reaction forces during starting motion. Force impulses from the hands, front foot and rearfoot were calculated via time integration. During the kick-start, the vertical impulse from the front foot was significantly higher than that from the rearfoot and the horizontal impulse from the rearfoot was significantly higher than that from the front foot. The force impulse from the front foot was dominant for generating vertical take-off velocity and the force impulse from the rearfoot was dominant for horizontal take-off velocity. The kick-start`s shorter block time in comparison to prior measurements of the grab start was explained by the development of horizontal reaction force from the hands and the rearfoot at the beginning of the starting motion.